Mitigating Ethno-Cultural Differences Ethical Guidelines for ICT Development in an Indigenous Community - Tariq, Zaman; Hasnain, Falak (IGI Global, 2017)
Community engagement is necessary for the success and sustainability of Information and Communication Technologies for Development (ICT4D) projects. To ensure active participation of community, researchers need to understand and adhere to the local cultural norms and adapt in the lifestyle of people. These cultural norms are mainly unwritten and implicit in nature. Hence the researchers spend maximum time of their field visits in observing and developing understanding of the community's life. In our long-term partnership with the indigenous Penan community of Long Lamai in Malaysian Borneo, we co-developed written guidelines for researchers and visitors. The researchers demonstrated their interest in aligning research process to the community's cultural values, however norm internalisation and development of associated behaviour is still a challenging. The written guidelines are yet only one of the attempts to the practices of community researchers' engagement and we are refining our methodology to enhance the researchers' learning process.